Evaluation of Sweet Pepper Varieties For Salinity Tolerance Based on Morpho- Physiological and Biochemical Attributes (SAARC Journal of Agriculture, 2023)
Soil salinity is a big threat to the world and has become a major concern to agricultural productivity. Sweet pepper (Capsicum annuum L.) is a high value vegetable; due to its quality nutrition. Despite growing all over the country, its production is not so high in Bangladesh. As a popular crop and also available everywhere, some varieties of sweet pepper were put under this study to assess their salt tolerance level. A pot experiment was conducted at net house, Botanical Garden, BAU, Mymensingh during the period from November, 2020 to April, 2021A factorial with CRD (Completely Randomized Design) was applied, where Factor A consisted of six sweet pepper varieties and Factor B included three salinity levels. In the vegetative stage, most of the parameters showed significant variation with salinity levels among varieties except chlorophyll content. In case of physio-morphological traits, all the parameters were significantly reduced with increasing salinity levels. In case of biochemical attributes, leaf proline contents were significantly increased with the higher level of salinity. Among six varieties being examined under the study, Messi had a relatively higher tolerance level than other varieties and therefore can be recommended for salt tolerance breeding studies.SAARC J. Agric., 21(1): 53-65 (2023)